Saved from a fatal flight: A ruptured splenic artery aneurysm in a pregnant woman. (2015) - Heitkamp, Anke C.; Dickhoff, Chris; Nederhoed, Johanna H.; Franschman, Gaby; de Vries, Johanna I.
Highlights: Although rupture of a splenic artery aneurysm is rare, its consequences can be devastating for both mother and child. Early recognition and prompt multidisciplinary treatment might save the life of mother and child. There is a difficulty in recognizing hemodynamic instability in pregnancy due to the increase in circulating volume. Abstract: Introduction: The reported prevalence of a SAA varies between 0.01 and 10.4% [1], and since SAAs often remain asymptomatic, the true prevalence is uncertain. The reported SAAs occur more frequently in younger patients, with 58% diagnosed in women of childbearing age; 95% of these are diagnosed during pregnancy. Presentation of case: A 26-year-old woman, thirty-one weeks pregnant, was about to board an airplane for a three hour flight from the Netherlands to Turkey. Just before entering the plane, she suddenly felt a severe abdominal pain. Ultrasound guided aspiration of the abdominal fluid showed blood and supported the decision to perform urgent laparotomy. A caesarean section was performed. After further inspection a ruptured SAA was encountered. The splenic artery was ligated proximally and distally to the rupture in order to stop the bleeding. As the hilar localization of the aneurysm interfered with a primary vascular reconstruction, a splenectomy was performed. The mother and baby survived. Discussion: Although rupture of a SAA is rare, its consequences can be devastating for both mother and child. The literature shows a higher incidence of ruptured SAA in pregnant women, although there is a difficulty in recognizing hemodynamic instability in pregnancy due to the increase in circulating volume. Conclusion: In case of pregnant women with acute abdomen and hypovolemia, emergency physicians, surgeons, anesthesiologists, and gynecologists should be aware of the possibility of a ruptured SAA, apart from more common causes like placental abruption, placenta percreta, or uterine rupture. Early recognition and prompt multidisciplinary treatment might save the life of mother and child.